Spectrophotometric Determination of Trace Amount of Nitrite in Water and Soil - Shakya, Sanjeela; D.C., Deepa; Chaudhary, Rajib; Gautam, Surendra K. (Academic View, Journal of TUTA Tri-Chandra Campus Unit, 2023)
A simple, sensitive, rapid and economical spectrophotometric method for the determination of trace amount of nitrite present in the water and soil samples is investigated. This method is based on the diazo-coupling reaction where nitrite reacts with p-nitroaniline in presence of hydrochloric acid to form diazonium cation which is subsequently coupled with 1-naphthol in presence of sodium hydroxide to form a stable azo-dye. The absorption maximum (λmax) for azo-dye is found to be 610 nm and the method obeys Beer-Lambert’s law at this analytical wavelength over the concentration range 0.02-0.12 μg/mL of nitrite. The molar absorptivity is found to be 3.29 x 104 liter.mol-1cm-1.